Entrepreneurship intention among the student’s college: shaperoentrepreneurial approach event model (case study at Borneo Tarakan university student) - Syahran Syahran; Aprina Patoding Kello (Faculty of Economics and Business Mulawarman University, 2022)
Aim research is to know the effect of attitude, the perceived desirability, the perceived feasibility toward the intention of Entrepreneurship by using theory approach of Shapero Entrepreneurial Event Model. The population of this research is all the students of Borneo University Tarakan by taken the sample 270 students from all faculties with the active criteria and already have taken the entrepreneurship department. The method of sampling was using Purposive Sampling by using data analyze method that consist of validity, reliability, and hypothesis and also helped by SmartPLS 3.0. The result of this research shows that: 1). The positive and significant influence of the attitude toward perceived desire, 2). The positive and significant influence of the perceived desire toward the Entrepreneurship Intention, 3). The positive and significant influence of the perceived worthiness toward the Entrepreneurship Intention. So, this case proves that the theory of Shapero Entrepreneurial Event Model which already used is able to explain the intention of entrepreneurship among the students college.